Pemberdayaan UMKM Telur Asin Melalui Sistem Akuntansi dan Strategi Pemasaran - As'adi; Hermi Sularsih; Sukarno Himawan Wibisono; Ahmad Mukoffi (WIDA Publishing, 2022)
Various parties responded to the economic situation in Indonesia. Each program is designed to address a certain issue, such as poverty. However, the proper approach to poverty alleviation has yet to be discovered. The lack of understanding of SME owners in various matters is one of the roadblocks to success in poverty alleviation efforts. One of the cases was found in salted egg SME owners’ lack of understanding on the accounting system in accordance with applicable standards. This situation has an impact on business continuity. It is necessary to empower them in the form of assistance and training for accounting systems for salted egg SMEs in Kecamatan Lowokwaru. The results of the community service show an increase in understanding of the accounting system and marketing strategy, which is hoped to help salted egg SMEs in the are grow in the future.